Different type of wood will affect the tone quality of electric guitar / Abdul Hakim Hashim. - Hashim, Abdul Hakim (2020)
What is electric guitar? Electric guitar is an instrument that is fretted and usually has six strings. Played with both hands by strumming or plucking the strings using either pick or the fingernails. Electric guitar is an instrument that use one or more pickups to convert the vibration of strings into electrical signals. The vibration occurs when a guitar player strums, plucks, fingerpicks, slaps or taps the strings. The pickup generally uses electromagnetic induction to create this signal, which being relatively weak is fed into a guitar amplifier before being sent to the speaker(s), which converts it into audible sound. The electric signal can be electronically altered to change the timbre of the sound. Often, the signal is modified using effects such as reverb, distortion, delay, chorus and "overdrive"; the latter is considered to be a key element of electric blues guitar music and rock guitar playing. The jazz guitar's player was adopted electric guitar, who wanted to play single-note solos in big band ensemble in 1931. The famous brand that was the early electric guitars that on record is Les Paul, Lonnie Johnson, Sister Rosetta Tharpe, T-Bone Walker, and Charlie Christian. Electric guitar became the most popular instrument music during 1950s and 1960s. It has evolved into an instrument that is capable of a multitude of sounds and styles in genres ranging from pop and rock to country music, blues and jazz. Electric guitar also become as a major instrument to develop blues, rock music, rock and roll, heavy metal, ballad and many other genres of music. Electric guitar design and construction varies greatly in the shape of the body and the configuration of the neck, bridge, and pickups. Electric guitars have fixed bridge and some of it have a spring that hinged the bridg, which let the players "bend" the pitch of notes or chords up or down, or perform vibrato effects. The electric guitar has variable type of techniques such as string bending, tapping, and hammering-on, using audio feedback, or slide guitar playing.